The Effect of The Company's Internal Factors on The Price Earning Ratio: Plantation Sub Sector Listed on The Indonesia Stock Exchange - Ulfha, Sri Maria; Surjono, Welly; Djulius, Horas (Adpebi International Journal of Multidisciplinary Sciences, 2024)
ABSTRACT Purpose – The purpose of this study is to determine how company size, corporate social responsibility and return on assets impact the price earninf ratio, either partially or simultaneously. Methodology/approach – The study population was 24 companies and samples were collected using the purposive sampling method, with a sample number of 9 companies with an 11-year study period. This research uses a data analysis method, namely panel data regression with the Eviews 10 program. Findings – The results of data processing show that company size, corporate social responsibility, return on assets simultaneously affect and significantly affect the price earning ratio. While some of the size of the company has a significant effect on the price earning ratio, corporate social responsibility has a significant effect on the price earning ratio and return on assets does not have a significant effect on the price earning ratio. Novelty/value – The value of research is the combination of various studies with research objects that are still rarely researched Keywords: Corporate Social Responsibility, Price Earning Ratio, Return On Assets, Company Size